Physical fitness of the top judoists in Japan - Sasa, T.; Shinozuka, T.; Kato, N.; Matsumoto, Y.; Ikai, M.; Asami, T.; Kaneko, M. (Association for the Scientific Studies on Judo, Kodokan, 1962)
In August last year (1961), the Society of Scientific Studies in Judo conducted a large scale survey of the physical fitness of the participants in the training camp sponsored by the Kodokan in order to fortify the candidates for the coming Olympic Games. As a result of this survey, many important data were obtained, together with many useful suggestions and problems. This year (1962) again, a similar training camp was held for two weeks in Numazu, Shizuoka Prefecture. Availing of this opportunity, we conducted a further over-all survey on the physical fitness of the athletes, on the first day. As regards items for measurement, reference was made to the results obtained last year, and in order to obtain a many-sided insight into the physical fitness of the athletes, careful selection of the items for measurement was made, and further items, such as leg strength, endurance, flexibility, and circulatory function were added.